FEED INDUSTRIAL MARKET IN THE YEARS 2005-2011 - Arkadiusz Piwowar (Journal of Agribusiness and Rural Development, 2013)
The article presents the carried out analysis of the feed industry in Poland in 2005-2011. The size and structure of industrial feed production and financial results of the national feed industry were presented. The retail prices of products of the relevant market and price relations for the selected industrial feed agricultural prices were analysed. As arises from the analyses, the industrial feed production in Poland increased in the examined period by 52%. With the increase in production, also significantly increased the feed retail prices.